Pengajaran Mazmur 114:1 dan Implikasinya Bagi Kehidupan Umat Tuhan Masa Kini - Rony Obed Oktafiano Manongko (Predica Verbum: Jurnal Teologi dan Misi, 2023)
This paper attempts to examine the theological value of Psalm 114:1 through a Biblical inductive hermeneutic study approach, relying on the procedures; morphological and grammatical-syntactic analysis of verse 1. The theological value is mainly about the principle of God's sovereignty and how it impacts modern Christian life. The text is seen to provide an important foundation for the Christian faith in understanding the sovereignty of the Lord God, through His existence and work in the life history of Old Testament Israel. The theological principles generated by the textual analysis procedure are seen to have parallels to the liberating work of God's people by Jesus Christ in the New Testament. With such understanding, God's people today will be able to endure in the hope of faith amidst the dynamics of contemporary challenges.